2022
DOI: 10.1590/1414-431x2022e12320
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of IL-12, IL-18, and IL-21 are indicators of viral load in patients chronically infected with HBV

Abstract: This study explored the correlation between interleukins (IL)-12, IL-18, and IL-21 and the viral load in patients with chronic hepatitis B virus (HBV). A total of 142 patients were consecutively enrolled. All were hepatitis B surface antigen (HBsAg)positive for 46 months and did not receive drug therapy. An ELISA kit was used to test the IL-12, IL-18, IL-21, and acetylcholinesterase (AchE) levels in serum samples from chronic HBV patients and healthy control groups. The amounts of IL-12 and IL-18 were highest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
0
0
Order By: Relevance
“…Intriguingly, in a study by Rossol et al comprising 72 patients with CHB, IL-12 levels were higher in patients when compared with healthy controls and, notably, IL-12 levels increased even further in patients under interferon treatment who showed virological response when compared to non-responders [132]. On the contrary, Zhou et al, in a cohort of 142 patients with CHB, showed that IL-12 levels were positively correlated with disease progression and could indicate disease severity for different HBV-DNA loads [133]. Finally, Du et al demonstrated that HBV-ACLF patients had higher IL-12 serum levels [134].…”
Section: Interleukin-12mentioning
confidence: 95%
“…Intriguingly, in a study by Rossol et al comprising 72 patients with CHB, IL-12 levels were higher in patients when compared with healthy controls and, notably, IL-12 levels increased even further in patients under interferon treatment who showed virological response when compared to non-responders [132]. On the contrary, Zhou et al, in a cohort of 142 patients with CHB, showed that IL-12 levels were positively correlated with disease progression and could indicate disease severity for different HBV-DNA loads [133]. Finally, Du et al demonstrated that HBV-ACLF patients had higher IL-12 serum levels [134].…”
Section: Interleukin-12mentioning
confidence: 95%